Ligament mechanics of ageing and osteoarthritic human knees - Abby E. Peters; Abby E. Peters; Brendan Geraghty; Karl T. Bates; Karl T. Bates; Riaz Akhtar; Rosti Readioff; Rosti Readioff; Rosti Readioff; Eithne Comerford; Eithne Comerford; Eithne Comerford (Frontiers in Bioengineering and Biotechnology, 2022)
Knee joint ligaments provide stability to the joint by preventing excessive movement. There has been no systematic effort to study the effect of OA and ageing on the mechanical properties of the four major human knee ligaments. This study aims to collate data on the material properties of the anterior (ACL) and posterior (PCL) cruciate ligaments, medial (MCL) and lateral (LCL) collateral ligaments. Bone-ligament-bone specimens from twelve cadaveric human knee joints were extracted for this study. The cadaveric knee joints were previously collected to study ageing and OA on bone and cartilage material properties; therefore, combining our previous bone and cartilage data with the new ligament data from this study will facilitate subject-specific whole-joint modelling studies. The bone-ligament-bone specimens were tested under tensile loading to failure, determining material parameters including yield and ultimate (failure) stress and strain, secant modulus, tangent modulus, and stiffness. There were significant negative correlations between age and ACL yield stress (p = 0.03), ACL failure stress (p = 0.02), PCL secant (p = 0.02) and tangent (p = 0.02) modulus, and LCL stiffness (p = 0.046). Significant negative correlations were also found between OA grades and ACL yield stress (p = 0.02) and strain (p = 0.03), and LCL failure stress (p = 0.048). However, changes in age or OA grade did not show a statistically significant correlation with the MCL tensile parameters. Due to the small sample size, the combined effect of age and the presence of OA could not be statistically derived. This research is the first to report tensile properties of the four major human knee ligaments from a diverse demographic. When combined with our previous findings on bone and cartilage for the same twelve knee cadavers, the current ligament study supports the conceptualisation of OA as a whole-joint disease that impairs the integrity of many peri-articular tissues within the knee. The subject-specific data pool consisting of the material properties of the four major knee ligaments, subchondral and trabecular bones and articular cartilage will advance knee joint finite element models.